Design of a scalable, flexible, and durable thermoelectric cooling device for soft electronics using Kirigami cut patterns. (21st January 2022) - Rosenberg, Z B; Weiner, N C; Shahariar, H; Li, B M; Peavey, J L; Mills, A C; Losego, M D; Jur, J S
Abstract: A flexible, soft thermoelectric cooling device is presented that shows potential for human cooling applications in wearable technologies and close-to-body applications. Current developments lack integration feasibility due to non-scalable assembly procedures and unsuitable materials for comfortable and durable integration into products. Our devices have been created and tested around the need to conform to the human body which we have quantified through the creation of a repeatable drape testing procedure, a metric used in the textile industry. Inspired by mass manufacturing constraints, our flexible thermoelectric devices are created using commercially available materials and scalable processing techniques. Thermoelectric legs are embedded in a foam substrate to provide flexibility, while Kirigami-inspired cuts are patterned on the foam to provide the drape necessary for mimicking the performance of textile and close to body materials. In total, nine different configurations, three different fill factors and three different Kirigami cut patterns were fabricated and inspected for thermal characterization, mechanical testing, flexibility and drape. Our studies show that adding Kirigami patterns can increase the durability of the device, improve the flexibility, decrease the drape coefficient, and have <1% of impact on cooling performance at higher fill factors (>1.5%), reaching temperature differences up to 4.39 °C ± 0.17 °C between the hot and cold faces of the device. These thermoelectric cooling devices show great flexibility, durability, and cooling for integration into soft cooling products.